Digital Transformation in Banking: Shielding Against Cyber Threats and Operational Risks - Maria Wati (Samarinda International Journal of Islamic Studies (SIJIS), 2024)
This paper examines the digital transformation currently reshaping the banking sector, focusing on the critical nexus of cybersecurity and operational risk management. The objective is to explore the multifaceted challenges and opportunities presented by this transformation, emphasizing the need for robust strategies to mitigate cyber threats and ensure operational resilience. The methodology involves a comprehensive literature review, synthesizing insights from academic journals, industry reports, and case studies. Key findings reveal that while digital transformation offers significant benefits such as enhanced efficiency and customer experience, it simultaneously expands the attack surface for cyber threats. The study highlights the increasing sophistication of cyberattacks and the growing reliance on digital infrastructure, emphasizing the importance of proactive security measures, including artificial intelligence (AI)-based solutions and blockchain technology. The paper concludes with recommendations for financial institutions to adopt a holistic approach to cybersecurity, integrating robust risk management frameworks, fostering collaboration, and investing in advanced technologies to safeguard against potential threats and ensure operational continuity.